Lu2CaMg2(Si1−xGex)3O12:Ce3+ solid-solution phosphors: bandgap engineering for blue-light activated afterglow applicable to AC-LED. Issue 43 (25th October 2016) - Lin, Hang; Wang, Bo; Huang, Qingming; Huang, Feng; Xu, Ju; Chen, Hui; Lin, Zebin; Wang, Jiaomei; Hu, Tao; Wang, Yuansheng
Abstract : "Bandgap engineering" is applied to design a new kind of Lu2 CaMg2 (Si1− x Ge x )3 O12 :Ce 3+ solid-solution phosphor applicable for low flickering AC-LED. Abstract : Persistent luminescence (PersL) has long commanded the curiosity of researchers owing to the complicated and profound physics behind it. In this work, the PersL mechanism in a new kind of persistent garnet phosphors, Lu2 CaMg2 (Si1− x Ge x )3 O12 :Ce 3+, is studied from the new perspective of a "solid-solution" scheme. Different from the conventional study in pursuit of long PersL, we focus on manipulation of afterglow to the millisecond range and tentatively demonstrate its potential to compensate the flickering of the alternating current driven LED (AC-LED) in every AC cycle. Evidently, the tailored host bandgap favors efficient electron charging and facilitates electron detrapping, as well as redeploying trap distribution, which results in a blue light activated afterglow in the millisecond time range, and subsequently a reduced percent flicker of 64.1% for the AC-LED. This investigation is the first attempt to establish the design guidelines for new PersL materials with an adjustable millisecond ranged afterglow, and, hopefully, it paves a pathway to the development of burgeoning low-flickering AC-LED technology.